Pathologic Risk Factors in Pediatric and Adolescent Patients With Clinical Stage I Testicular Stromal Tumors. Issue 8 (November 2015) - Rove, Kyle O.; Maroni, Paul D.; Cost, Carrye R.; Fairclough, Diane L.; Giannarini, Gianluca; Harris, Anne K.; Schultz, Kris A. P.; Cost, Nicholas G.
Abstract : Background: Testicular stromal tumors (TSTs) are rare. In adult men with TSTs, various pathologic risk factors have been identified in patients with clinically localized disease that increase the risk of occult metastatic disease (OMD). We systematically reviewed existing literature to analyze the impact of these risk factors on OMD in prepubertal (0 to 12 y) and postpubertal (13 to 21 y) patients. Methods: A literature search was conducted using the combination of terms: "testicular stromal tumors, " "testicular leydig cell tumors, " "testicular sertoli tumors, " "testicular interstitial tumors, " "testicular granulosa tumor, " and "testicular sex cord tumors." Studies of patients 0 to 21 years with clinical stage I TSTs were included. Results: A total of 100 patients from 31 publications were included with a median age at diagnosis of 5.7 years (range, 1.2 mo to 21 y). Seventy-nine patients were 12 years and below (median 7.2 mo) and 21 patients were 13 to 21 years (median 16 y). No patients in either group were identified to have OMD at retroperitoneal lymph node dissection or during follow-up surveillance (median follow-up 45.6 y; range, 4 to 360 mo). 99% of those 12 years and below versus 95% of those above 12 years had 0 to 1 pathologic risk factors, and 1% versus 5% had 2+ pathologic risk factors ( P =0.38). Conclusions: Clinical stage I TSTs in adolescent, postpubertal patients appear to behave in a benign manner with few pathologic risk factors, similar to prepubertal patients. Given the low risk of relapse in this population, low-impact surveillance strategies are paramount. Prospective study of these patients is needed, and entry into a tumor registry such as the International Ovarian and Testicular Stromal Tumor Registry is important to learning more about this rare disease.